PENDAMPINGAN DAN PEMBINAAN KELOMPOK SMART EDUKASI KESEHATAN DALAM PENCEGAHAN STUNTING DI DESA SARI MULYO KECAMATAN SUKARAJA KABUPATEN SELUMA - Kamsiah Kamsiah; Emy Yuliantini; Tonny C. Maiggoda; Yusmidiarti Yusmidiarti; Wewet Savitri (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Partners in this community service program are the Seluma District Health Office, the Community Health Center and the Village Head. The community regional partnership program(PKW) aims to provide knowledge as well as training in SMART mentoring and coaching to cadres and mothers of toddlems found related to SMART mentoring and coaching for the SMART Health Education Group in Stunting Prevention in Seluma District. The problems found among others .1.knowledge about Stunting Prevention activitas owned by the SMART Cadres team group which is still limited, 2. Knowledge possessed by Cadres in hereditary infomation meaning that activities are still based on correct know ledge, 3.Mastery of drafting techniques and implementation of activities must still be adjusted to good and correct standars, 4. Various errors, both related to the procces, evaluation monitoring and follow- up stunting prevention activities are still not effective, 5. The lack of references regarding the implementation of activities. The solution offered is to share knowledge related to Health Education SMART Group Assistance and Development in Stunting Prevention in Seluma Regency through activites, training, mentoring, and evaluation of the application of the existing Health Education SMART Group program. The output targest are scientifc publication in journals with ISSN/ proceeding, publication through online media, and improvement of science and technology fpr the community. To achieve this goal, the service team uses a chronological strategy, with the sequence of implementation starting from questions and answers providing material, practive and evaluating the results of practice.